PENINGKATAN LAYANAN SISTEM INFORMASI AKADEMIK BERBASIS ANDROID ( STUDI KASUS DI STTA YOGYAKARTA) - Tirta, Akbar Maulana; Sumarsono, Sumarsono; Honggowibowo, Anton Setiawan (Compiler, 2012)
Academic information systems have a goal for facilitate students in to access there are information. But facilities which has given by college not yet maximum. With utilize smartphone based on android, students can be access there are Academic information systems. Client Server become solution method for implement Academic information systems to the smartphone.This Academic information systems use database PostgreesSQL, it which implanted in server and become smartphone android have been installed  Academic information systems application , it’s become client. Academic information systems application have many feature among other input KRS, view course value, view attendance and course schedule, with there are feature it, so will increase Academic information systems service.